2021
DOI: 10.1371/journal.pone.0252518
|View full text |Cite
|
Sign up to set email alerts
|

Could teacher-perceived parental interest be an important factor in understanding how education relates to later physiological health? A life course approach

Abstract: Education is associated with later health, and notably with an indicator of physiological health measuring the cost of adapting to stressful conditions, named allostatic load. Education is itself the result of a number of upstream variables. We examined the origins of educational attainment through the lens of interactions between families and school i.e. parents’ interest in their child’s education as perceived by teachers. This study aims to examine whether parental interest during a child’s educational traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The relationship between educational categories (no diploma for men and baccalaureate, vocational certi cate/quali cation and no diploma for women) and anxiety-depressive score was not fully explained. This persistent association may be explained by earlier or dynamic processes in individuals' lives corresponding to early factors hidden by education (31,53). Differences observed between men and women, with a steeper gradient for women, point to social inequalities in health that may be related to a gender effect (54) previously highlighted in this study population (55).…”
Section: Discussionmentioning
confidence: 60%
“…The relationship between educational categories (no diploma for men and baccalaureate, vocational certi cate/quali cation and no diploma for women) and anxiety-depressive score was not fully explained. This persistent association may be explained by earlier or dynamic processes in individuals' lives corresponding to early factors hidden by education (31,53). Differences observed between men and women, with a steeper gradient for women, point to social inequalities in health that may be related to a gender effect (54) previously highlighted in this study population (55).…”
Section: Discussionmentioning
confidence: 60%
“…The relationship between educational categories (no diploma for men and baccalaureate, vocational certificate/qualification and no diploma for women) and anxiety-depressive score was not fully explained. This persistent association may be explained by earlier or dynamic processes in individuals' lives corresponding to early factors hidden by education [29,51]. This may be also explained by a low sense of personal control [19] or challenges in health-related knowledge or health literacy [52], affecting the ability to cope with stress and adopt coping behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, parental interest in their child’s education has been reported as an upstream determinant of education having lasting effects on health. 38 , 39 Moreover, the socio-economic mix of schools and the educational expectations within schools may influence social class differences in educational achievement. 40 Thus, apart from studies focusing on education at individual or interpersonal levels, further research focusing on education at system/organization or community levels is needed.…”
Section: Neglected Aspects Of Educationmentioning
confidence: 99%